Contaminant Delineation of a Landfill Site Using Electrical Resistivity and Induced Polarization Methods in Alice, Eastern Cape, South Africa - S. Mepaiyeda; K. Madi; O. Gwavava; C. Baiyegunhi; L. Sigabi (International Journal of Geophysics)
A combination of electrical resistivity and induced polarization methods were applied to a solid waste landfill in Alice, Eastern Cape, South Africa to delineate the lithologic layers and locate possible leachate plumes. Resistivity and IP data were collected along six profiles; VES on two and the dipole-dipole configuration was used in the rest four. The result shows a 4-layered earth system with a shallow depth to the top of the bedrock (<10 m). Contaminants ranging from unsaturated waste with high ion content to dense aqueous phase liquid contaminants, characterized by low resistivity (34–80 Ohm-m) and low chargeability values (0.05–5.75 ms). The contamination was interpreted based on resistivity/IP anomalies considering the background geology. The shallow bedrock indicated a low risk to groundwater contamination because of its competent nature from its geology, and characteristic high resistivity values (≥1000 Ohm-m). However, the steep nature of the landfill terrain due to its location at the foot of a vertical slope favours the rapid migration of the contaminants into the immediate vicinity of the landfill. The construction of containment structures such as waste cells will help in enhancing effective waste management practices in the landfill.